Fintech as a Building Block of the Financial Ecosystem in India - Gaba, Piyush (Digital Repository of Theses, 2024)
The financial technology (fintech) revolution in India has become a driving force in the country's economic landscape. This research looks into the evolving fintech scene in India, exploring its use, obstacles, limits, influence on financial literacy, and customer trust. Purpose: The primary aim of this research is to provide a comprehensive understanding of fintech's role in India's financial ecosystem, with a specific focus on identifying regulatory hurdles, infrastructure deficiencies, and their impact on fintech adoption. Additionally, the study examines the relationship between financial literacy and fintech usage while delving into factors influencing consumer trust in fintech services. Methods: This research used a quantitative approach and surveys people who have used fintech in India. Three hundred people were surveyed with a questionnaire. Ordinal regression and correlation analysis, among other statistical methods, are used to examine the data and develop conclusions. Results: Several major takeaways may be drawn from the study's results. Complex compliance processes and strong know-your-customer standards are cited as major barriers to adoption of fintech. The smooth implementation of fintech services is hampered by infrastructure, especially poor internet access, in rural regions. The necessity of financial education programmes is emphasised by the study's positive finding that participants' levels of financial literacy were associated with greater use of fintech. In addition, the findings reveal a considerable correlation between consumer trust concerns and the use of fintech, underscoring the importance of strong cybersecurity measures and open data handling policies. Conclusions: In conclusion, this research highlights the importance of fintech in transforming India's financial industry and expanding access to financial services for the country's underserved population. In order to encourage innovation while protecting consumers, regulatory agencies should work actively with fintech players. To close the digital divide between cities and the countryside, investments in digital infrastructure are crucial. For fintech to be widely adopted, financial literacy must be improved, and fintech platforms must prioritise trust-building methods to win over and keep customers. The research contributes to the development of a robust and inclusive fintech ecosystem in India by offering practical recommendations for policymakers, financial institutions, fintech firms, and consumers.